Legal issues related to the concept of the placing food on the market - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2023)
The aim of the considerations is an attempt to answer the question of whether the concept of food marketing includes the specificity of foodstuffs, the need to ensure special consumer protection, or the challenges of modern times related to the need to ensure food safety. While the author answers this question positively, he notes that in legislative acts on food law and food marketing it is understood in different ways. This, together with the imprecision of the provisions of national and EU regulations concerning the concept of placing food on the market, may create significant interpretative problems and result in the hindering of the application of the law. In consequence, the regulations under review may not fully address the challenges of modern times or the need to ensure food security which intended to be achieved through, among other things, new technologies and innovative methods of food production, an introduction for human consumption of previously unknown foodstuffs and a further reduction of food waste.